PEMANFAATAN IOT PADA KOLAM AQUARIUM UNTUK BUDIDAYA IKAN - Dendy Kurniawan; Edy Siswanto; M Rifaldi Pratama (Informatika: Jurnal Teknik Informatika dan Multimedia, 2024)
The internet of things system aims to facilitate its users and also lighten human work to be more efficient, practical and can be easily controlled using a smartphone. This study aims to create an IoT system for aquarium ponds for cultivation in betta fish farming and its location is in the city of Semarang, more precisely in the village of Lempongsar Semarang. With the implementation of this IoT system, it is expected to help the cultivation of betta fish to the maximum. From the results of the study, the system can be used well, which is proven by the results obtained from the expert validation test, namely 75% which means valid. Because it is located in the validity criteria of 51% -75%. The results obtained from the validation test of betta fish farming managers are 80% which means very feasible. Because it is located in the feasibility criteria of 76% -100%